Epiphytic Orchid Diversity in UB Forest and Opportunities for Orchid Tourism Road Development - Gheavanda Putri Rahadi; Luchman Hakim (Graduate Program, 2018)
The aims of the research were to identify epiphytic orchid diversity and host tree species for the development of orchid tourism trails as a potential tourist attraction in UB Forest. A Floristic survey and questionnaires were conducted in this study. Nine epiphytic orchids were found in UB Forest, namely Liparis viridiflora, Eria hyacinthoides, Aerides sp., Coelogyne sp., Dendrobium lineairifolium, Agrostophyllum sp., Sarcanthus sp., Flickingeria sp. and Eria monostachya. These epiphytic orchids used Dadap (Erythrina sp.), Jalina (Ficus sp.), Kukrup (Engelhardtia spicata) and Cempaka wangi (Michelia champaca) as host species, from Gate 1 to Gunung Mujur Point in UB Forest. Analysis showed that improvement including preserving and improving the population of host tree species, establishing interpretation media for educational purposes, and improving the attractiveness of tourist attractions and facilities, could provide an opportunity to develop an eco-tourism route.Keywords: Ecotourism, Environmental education, Orchids